Users’ Experiences in Using Book Creator for Creative and Innovative Learning - Hayati, Noor (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Within the 21st century learning framework, the blueprint of education in the future making the hybrid learning model ideal option including in learning English. In English learning, using certain kind of technology is important for creative and innovative learning and the students must take into account to decide their own learning model and media. This study aimed at exploring users’ Experiences in using “Book Creator” for creative and innovative English learning. Quantitative descriptive research was conducted to 26 students of English class as the users of Book Creator. Six scales of User Experience Questions (UEQ) were used and analyzed using UEQ tool. Generally, the participants responded positively towards the use of Book Creator in English learning. The level of users’ experiences in using Book Creator with an average scale of test result on six scales; attractiveness 1.667, Perspicuity 1.440, Efficiency 1.340, Dependability 0.620, Stimulation 1670, Novelty 1.070. The highest scale was on the stimulation scale at 1.670 which was categorized as “Excellent” while the lowest score was the Dependability at 0.620 which was categorized “bad”. In short, there is positive experience of the users in using Book Creator for learning and the alternative hypothesis is accepted